Sex-related differences in self-reported treatment burden in patients with atrial fibrillation - Mihajlovic, Miroslav; Simic, Jelena; Marinkovic, Milan; Kovacevic, Vladan; Kocijancic, Aleksandar; Mujovic, Nebojsa; Potpara, Tatjana S. (Frontiers in Cardiovascular Medicine, 2022)
Background: Treatment burden (TB) is defined as the patient's workload of health care and its impact on patient functioning and well-being. High TB can lead to nonadherence, a higher risk of adverse outcomes and lower quality of life. We have previously reported a higher TB in patients with atrial fibrillation (AF) vs. those with other chronic conditions. In this analysis, we explored sex-related differences in self-reported TB in AF patients. Methods: A single-centre, prospective study included consecutive patients with AF under drug treatment for at least six months before enrolment from April to June 2019. Patients were asked to voluntarily and anonymously answer the Treatment Burden Questionnaire (TBQ). All patients signed the written consent for participation. Results: Of 331 patients (mean age 65.4 ±10.3 years, mean total AF history 6.41 ±6.62 years), 127 (38.4%) were females. The mean TB was significantly higher in females compared to males (53.7 vs. 42.6 out of 170 points, p<0.001), and females more frequently reported TB ≥59 points than males (37.8% vs. 20.6%, p=0.001). In females, on multivariable analysis of the highest TB quartile (TB ≥59), non-vitamin K Antagonist Oral Anticoagulant use (Odds Ratio [OR] 0.319; 95% Confidence Interval [CI] 0.12-0.83, P=0.019), while in males, catheter ablation and/or ECV of AF (OR 0.383; 95% CI 0.18-0.81, P=0.012) were negatively associated with the highest TB quartile. Conclusion: Our study was the first to explore the sex-specific determinants of TB in AF patients. Females had significantly higher TB compared with males. Approximately 2 in 5 females and 1 in 5 males reported TB ≥59 points, previously shown to be an unacceptable burden of treatment for patients. Using a NOAC rather than VKA in females and a rhythm control strategy in males could decrease TB to acceptable values.